DUKUNGAN SISTEM PENYELENGGARAAN BIMBINGAN DAN KONSELING DI SEKOLAH MENENGAH KECAMATAN SEKAMPUNG - Wita Febritus; Syarifuddin Dahlan; Muswardi Rosra (ALIBKIN (Jurnal Bimbingan Konseling), 2014)
The purpose of this research was to describe aspects of the guidance and counseling support system. This research is using survey method, with interviews and observations as data collection techniques. The sources are 24 counselor. Data analysis technique use percentage descriptive. The results are the guidance and counseling support system is a collaboration counselor with teacher for the study in the handling of students who have trouble learning (87,5%), collaboration counselor with the parents of students in order to data collection of students learning activities at home (87,5%), collaboration counselor with psychologist to the psychological tests (0%), counselor activeness teacher in ABKIN (41,7%), the special room of guidance and counseling (11.1%), an instrument of AUM (41,7%), complete counseling program documents (50%), technical supporting that is computer (62,5%), the allocation of funds for home visit (54,2%), and scheduled time allocation is 1 hours/sunday/classes for guidance class. (16,7%).Penelitian ini bertujuan mendeskripsikan aspek-aspek dukungan sistem penyelenggaraan bimbingan dan konseling. Menggunakan metode survey, dengan wawancara dan observasi sebagai teknik pengumpulan datanya. Informannya 24 orang guru BK. Teknik analisis data menggunakan deskriptif persentase.Hasilnya, aspek-aspek dukungan sistem adalah kolaborasi guru BK dengan wali kelas/guru bidang studi dalam penanganan siswa yang memilikiprestasi belajar rendah (87,5%), kolaborasi guru BK dengan orang tua siswa dalam rangka pengumpulan data kegiatan belajar siswa di rumah (87,5%), kolaborasi guru BK dengan psikolog untuk pengadaan tes psikologi (0%), keaktifan guru BK dalam ABKIN (41,7%), adanya ruang khusus BK (11,1%), instrumen pengumpul data AUM (41,7%),dokumen program BK lengkap (50%), penunjang teknis komputer (62,5%), alokasi dana untuk home visit (54,2%) dan alokasi waktu terjadwal 1 jam pelajaran/minggu/kelas untuk bimbingan klasikal (16,7%).Kata kunci: bimbingan dan konseling, dukungan sistem, penyelenggaraan